Evaluation of Thermal Stress and Performance for Solid Oxide Electrolysis Cells Employing Graded Fuel Electrodes - Fangzheng Liu; Liusheng Xiao; Ruidong Zhou; Qi Liu; Jinliang Yuan (Energies)
An electrochemical reactions coupled multi-physics model is developed and applied to elucidate overall performance and thermal stress distributed in solid oxide electrolysis cells (SOECs) with graded fuel electrodes. Extending the conventional fuel electrode, the effects of various graded parameters are investigated and discussed in terms of porosity, pore size, and material composition, with the goal of identifying characteristics of the hydrogen production rate and maximum thermal stress. The results show that the application of the graded parameters is able to optimize the gas distribution and to improve reaction kinetics, avoiding local overheating. The generated hydrogen molar fraction is enhanced by 15.6% while the maximum thermal stress is decreased by 5.0% if the graded parameters are applied, while changing the material composition may increase the thermal stress under the same circumstances. These explorations elucidate the complex role of the graded fuel electrodes on the electrolysis and thermomechanical properties of SOECs.